2014
DOI: 10.5812/hepatmon.17323
|View full text |Cite
|
Sign up to set email alerts
|

Serological Assay and Genotyping of Hepatitis C Virus in Infected Patients in Zanjan Province

Abstract: Background:Hepatitis C Virus (HCV), a public health problem, is an enveloped, single-stranded RNA virus and a member of the Hepacivirus genus of the Flaviviridae family. Liver cancer, cirrhosis, and end-stage liver are the outcomes of chronic infection with HCV. HCV isolates show significant heterogeneity in genetics around the world. Therefore, determining HCV genotypes is a vital step in determining prognosis and planning therapeutic strategies.Objectives:As distribution of HCV genotypes is different in vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 37 publications
(32 reference statements)
1
0
0
Order By: Relevance
“…Genotype 6 prevails in Hong Kong and Vietnam. 36 In our study, male dominance was observed with seropositivity of 63.63% and is in agreement with the studies from Uttarakhand, Delhi, and Haryana. 37,38 Another study from Delhi revealed the male preponderance with overall male to female ratio of 1.5:1.…”
Section: Discussionsupporting
confidence: 92%
“…Genotype 6 prevails in Hong Kong and Vietnam. 36 In our study, male dominance was observed with seropositivity of 63.63% and is in agreement with the studies from Uttarakhand, Delhi, and Haryana. 37,38 Another study from Delhi revealed the male preponderance with overall male to female ratio of 1.5:1.…”
Section: Discussionsupporting
confidence: 92%